DEVELOPMENT OF A WEB-BASED PURCHASE ORDER SYSTEM IN THE PURCHASING DIVISION USING THE AGILE MODEL (CASE STUDY: CV KLAMBY) - Fauziah Ika Mawarni; Fahrul Razi (Yayasan Adra Karima Hubbi, 2025)
This study aims to design and develop a web-based purchase order (PO) system equipped with an integrated approval feature by implementing the Agile development methodology. Agile is chosen for its iterative, flexible, and user-oriented development approach. The research follows several stages, including planning, requirements analysis, system design, development, testing, implementation, and evaluation. The system was developed using JavaScript (Node.js) and MySQL, and tested through blackbox testing. The results show that the system effectively facilitates PO creation, vendor and product data management, and supports secure, automated multi-level approval. The implementation of this system has been proven to enhance the efficiency and accuracy of procurement processes, reduce human error, and provide better-organized documentation. This system is expected to serve as a digital solution that can be adopted by other companies and strengthen the application of Agile methodology in information system development projects.